2016
DOI: 10.1002/acr.22795
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Calprotectin Versus Acute‐Phase Reactants in the Discrimination of Inflammatory Disease Activity in Rheumatoid Arthritis Patients Receiving Tumor Necrosis Factor Inhibitors

Abstract: Objective. To compare the accuracy of serum calprotectin and acute-phase reactants (C-reactive protein [CRP] and erythrocyte sedimentation rate [ESR]) in stratifying disease activity in rheumatoid arthritis (RA) patients receiving tumor necrosis factor inhibitors (TNFi), and to correlate calprotectin levels with TNFi trough serum levels. Methods. We conducted a cross-sectional study of 87 RA patients receiving adalimumab, etanercept (ETN), or infliximab (IFX); 56 psoriatic arthritis (PsA) patients and 40 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
2
34
0
2
Order By: Relevance
“…CALP is a potent activator of innate immunity mediated through Toll-like receptor 4 (9) and is primarily a product of neutrophils. Elevated serum CALP levels are associated with inflammatory diseases (10,11), while fecal CALP assays are widely used to differentiate inflammatory bowel disease from irritable bowel syndrome and ulcerative colitis (12). In the present study, we confirm that serum CALP levels are elevated in NHPs with respiratory infections caused by B. pseudomallei and examine the possibility of using CALP as a general biomarker for clinical responses during the acute and eradication phases of antibiotic treatment in human cases of melioidosis.…”
supporting
confidence: 69%
“…CALP is a potent activator of innate immunity mediated through Toll-like receptor 4 (9) and is primarily a product of neutrophils. Elevated serum CALP levels are associated with inflammatory diseases (10,11), while fecal CALP assays are widely used to differentiate inflammatory bowel disease from irritable bowel syndrome and ulcerative colitis (12). In the present study, we confirm that serum CALP levels are elevated in NHPs with respiratory infections caused by B. pseudomallei and examine the possibility of using CALP as a general biomarker for clinical responses during the acute and eradication phases of antibiotic treatment in human cases of melioidosis.…”
supporting
confidence: 69%
“…In addition, calprotectin and S100A12 can be chemoattractants for neutrophils and monocytes/mast cells, respectively [7] and can thus in several ways contribute to recruitment of leukocytes to inflammatory sites. Both proteins have, when measured in plasma or serum, been repeatedly reported to be associated with clinical disease activity in RA [8–18]. In addition, calprotectin was associated with radiographic damage in a cross-sectional study and predicted radiographic progression in a longitudinal study [11, 19], whereas S100A12 has shown a weak association with radiographic damage in a small longitudinal study [17].…”
Section: Introductionmentioning
confidence: 99%
“…Inciarte-Mundo et al [17] in a cross-sectional study included 87 patients with rheumatoid arthritis, receiving adalimumab, etanercept or infliximab for at last 3 months. They demonstrated that calprotectin stratified disease activity in rheumatoid arthritis patients receiving TNF-α inhibitors more accurately than the acute-phase reactants such as CRP and erythrocyte sedimentation rate (ESR), whichever composite index was assessed (the Disease Activity Score in 28 joints [DAS28], the Clinical Diseases Activity Index [CDAI] or the Simplified Disease Activity Index [SDAI]).…”
mentioning
confidence: 99%
“…Only calprotectin level distinguished between RA patients in clinical remission and those with low disease activity according to all indices analyzed. MRP8/14 serum level correlated inversely with TNF-α inhibitors trough serum levels [17]. In another study, Inciarte-Mundo et al [18] analyzed associations between calprotectin, ESR, CRP and disease activity indices in 33 RA patients receiving tocilizumab.…”
mentioning
confidence: 99%